No 'Emperor of Europe': A Rare Title between Political Irrelevance, Anti-Ottoman Polemics and the Politics of National Diversity. (October 2017) - Oschema, Klaus
Recent research on the use of the notion of Europe during the Middle Ages has confirmed that the name of the continent only rarely acquired a political meaning, if at all, in this period. What is particularly surprising is the observation that several authors in the Latin world used expressions such as regnum Europae or regna Europae, especially in the Carolingian period, without elaboration. Hence, although Charlemagne has been praised as 'father of Europe' by one contemporary author, the idea of an 'Emperor of Europe' was never developed, with the exception of two brief notices in early medieval Irish annalistic compilations. Even during the High Middle Ages, when the name of the continent came to be more widely used in different contexts, only a small set of figures, historical as well as fictitious, were ascribed with the aspiration or quality of ruling all of Europe.  Towards the end of the Middle Ages, however, the notion of an 'Emperor of Europe' became more common in a particular context: Christian authors accused non-Christian rulers of Asian origin (Mongols, Turks) of seeking to subdue the entire continent. Latin authors, in turn, started to perceive Europe as being the home of Christendom.  This article demonstrates how those Christian authors accept a pluralistic order for their own continent (on a political level), and contrasts this with the quest for hegemonic rule that becomes a motive of polemic, which they ascribe to non-Christian rulers. Although their arguments do not lead to the explicit presentation of Europe as the 'continent of freedom', they do recognise and value the existence of a multitude of political entities which they contrast with a hegemonic and homogenous political role of 'Asian tyrants'. In a broader perspective, these findings open insights into late medieval political thought that go beyond what we can learn from contemporary 'political discussion' in a more limited sense.